Efektivitas Program Keluarga Harapan Dalam Penanggulangan Kemiskinan - Ema Fitri Lubis; Evi Zubaidah (Universitas Musamus, Merauke, Papua, 2020)
Poverty is still the biggest challenge in Indonesia today. It is closely related to health, education, toddlernutrition, etc. Numerous policies have been rolled out by the government to overcome this problem. Oneof them is Program KeluargaHarapan (PKH) from the Ministry of Social Affairs Republic of Indonesia.This research aims to find out the effectiveness of Program KeluargaHarapan in reducing the number ofpoverty and the inhibiting factors in implementing the program in KecamatanTenayan Raya, KotaPekanbaru. This research is using a quantitative method with a descriptive approach. The results of thisresearch are classified into three categories: effective, quite effective, and less effective. The respondentscategorized the input, process, and output of the program to be effective. 72% of 30 respondents thinkthat the input approach is effective. It means that the PKH implementation in the KecamatanTenayanRaya is following the objectives of the program. 71% of the respondents consider that the process of PKHaid distribution is following the Standard Operating Procedures. Besides, 77% of them think that thefamily who received support from the program met the proper criteria. Regarding the inhibiting factorsof this program, the respondents emphasized several aspects. The inhibiting factor for the effectivenessof this family expectation program includes; the lack amount of money given to the community; and poorcoordination between program officers and supervision.